2015
DOI: 10.1308/rcsann.2015.0020
|View full text |Cite
|
Sign up to set email alerts
|

From guidelines to standards of care for open tibial fractures

Abstract: These findings vindicate the Standards as well as mandating reorganisation and resourcing of orthoplastic services to ensure immediate transfer and early combined surgery. By increasing the capacity to deal with time-dependent initial surgery, the surgical burden that the patient must endure, and which the service must provide, are reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Thus, we performed skin grafting when bones were covered with muscle and soft tissue. According to British Association of Plastic, Reconstructive and Aesthetic Surgeons guidelines [20], open fractures should be covered within 5-7 days after injury. In this study, the timing of wound closure of the infection group was longer than that recommended, as some patients required NPWT to improve their wound conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we performed skin grafting when bones were covered with muscle and soft tissue. According to British Association of Plastic, Reconstructive and Aesthetic Surgeons guidelines [20], open fractures should be covered within 5-7 days after injury. In this study, the timing of wound closure of the infection group was longer than that recommended, as some patients required NPWT to improve their wound conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cognizant of its importance, the British Association of Plastic, Reconstructive and Aesthetic surgeons (BAPRAS) and the British Orthopaedic Association together introduced guidelines to improve the management of complex tibial fractures in 1997 [13]. Surprisingly, several authors have reported that awareness of and adherence to these recommended standards was poor, with no significant changes noted in the last decade [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In common with other studies, we have shown support for an orthoplastics service following the introduction of the trauma network. [12][13][14][15][16][17][18][19] Plastic surgical involvement is an integral factor in major trauma service planning and provision from postgraduate training to the provision of joint orthoplastics operating lists. The reduction we identified in the number of patients undergoing skeletal stabilisation and who later underwent soft-tissue coverage suggests a coordinated orthoplastic service.…”
Section: Discussionmentioning
confidence: 99%